Community Models As Partners Effective To Increase The Quality Of Life Of Hypertension Patients - Emdat Suprayitno; Dian Permatasari; Zakiyah Yasin (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Quality of life is still the main problem determining hypertensive patients' recovery, where it is found that the quality of life is still low. Community models as partners in intervention strategies are urgently needed to increase the quality of life. Methods: The design of this study was quasi-experimental. The population is 60 people with hypertension with simple random sampling. The total sample is 60 people divided into two groups: the treatment group, 30 people given caring-based supportive educative intervention, and 30 people in the control group given pamphlets about hypertension. Results: Based on research based on the Wilcoxon test, the quality of life score in the intervention group after the intervention was provided, namely p = 0.000, and based on the Mann-Whitney test, the quality of life score in the control group and treatment group after the intervention was given, namely p = 0.002. The results of this study showed that community as a partner model intervention was effective in improving the quality of life of hypertensive patients. Conclusion: The community model as a partner model intervention has an effect on the quality of life of hypertensive patients.